A mechanosensitive vascular niche for Drosophila hematopoiesis. - Tian, Y.; Morin-Poulard, I.; Liu, X.; Vanzo, N.; Crozatier, M. (Proceedings of the National Academy of Sciences of the United States of America, 2023)
Hematopoietic stem and progenitor cells maintain blood cell homeostasis by integrating various cues provided by specialized microenvironments or niches. Biomechanical forces are emerging as key regulators of hematopoiesis. Here, we report that mechanical stimuli provided by blood flow in the vascular niche control Drosophila hematopoiesis. In vascular niche cells, the mechanosensitive channel Piezo transduces mechanical forces through intracellular calcium upregulation, leading to Notch activation and repression of FGF ligand transcription, known to regulate hematopoietic progenitor maintenance. Our results provide insight into how the vascular niche integrates mechanical stimuli to regulate hematopoiesis.